Dependence of socio-economic processes on the human capital development - Pestrikova E. A. (Interactive science, 2018)
the article examines the dependence of socio-economic processes on the human capital development. The authors concluded that improving the quality of human capital, the level of knowledge and the formation of labor are the main guarantee of labor productivity and the growth of employment in the Russian Federation.
Keywords: организация; экономика; обучение; инновация; человеческий капитал; социум; эффективность; подходы; training; organization; efficiency; Society; innovation; economics; human capital; approaches